The Effect of Fiscal Policy Shocks on Private Expenditure: A SVAR Study in Indonesia - Kaharudin, Iszan Hana; Rahman, Mohd Syuhaimi Ab (Journal of Ecohumanism, 2024)
This paper examines the effect of fiscal policy on private expenditure in a small open economy (i.e., Indonesia) through an open economy structural VAR (SVAR) study. The data set comprised a quarterly time series spanning from 2000:1-2022:4. Impulse response function (IRF) and variance decomposition (VDC) were used to analyze the effect of fiscal policy shocks on private expenditure. The main results indicated that government spending shocks crowded out private consumption. Domestic income gave a similar negative effect that can be explained by Ricardian equivalence theory which showed a reduction in private consumption. The effect of government tax revenue on private consumption was positive. The results supported the non-Keynesian effect which suggested that the increase in government tax revenue tended to increase private consumption. Similarly, domestic income showed a positive effect.